PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR TAHUN 2011-2013 - Ernie Riswandari (Jurnal Akuntansi Bisnis, 2017)
This research aims to scrutinize about the influence of corporate social responsibility ( CSR ) against tax aggressiveness on industry manufacturing sector years 2011-2013 with the use of variable control namely profitability control and leverage. The data used in this research is taken from secondary data in the form of annual report the company. Investigation at the data was done using regression test. The result of taxes that tax aggressiveness committed by a corporate not because of its profits gained a company and is not affected by the leverage that the capital which is owned by the company.While to the influence of corporate social responsibility ( CSR ) against tax aggressiveness obtained the results of the higher the disclosure of corporate social responsibility ( CSR ) undertaken company tax hence aggressiveness done by companies getting high but his influence is not significant Key Word : Corporate Social Responsibility (CSR), Effective Tax Ratio (ETR),Return on Asset, Leverage